Anthropometry of world-class elite handball players according to the playing position: Reports from men's Handball World Championship 2013 - Ghobadi, H.Z.; Rajabi, H.; Farzad, B.; Bayati, M.; Jeffreys, I. (Journal of Human Kinetics, 2013)
Identifying the anthropometric measures of successful and less successful handball players may be helpful in developing a talent identification and development model, allowing for the determination of key physical capacities required for elite performance. The purpose of the study was to describe the anthropometric characteristics, including age, standing stature, body mass and body mass index (BMI) in handball players who participated in the 2013 Men's Handball World Championships. Secondly, the objective was to identify the possible differences in these parameters in terms of individual playing positions (goalkeeper, back, center back, wing, line player). Rosters with handball player's age, standing stature, and body mass were obtained from the International Handball Federation website. The research material included 409 handball players (24 teams). National teams were organized by their ranks and sub-grouped using their continents and playing positions. The results of the analyses of variance demonstrated significant differences in age (F=2.30; p=0.044; Partial 2=0.028), standing stature (F=14.02; p=0.0001; Partial 2=0.148), and body mass (F=5.88; p=0.0001; Partial 2=0.068) among the groups (G1-G6). Players in G1 had the highest standing stature and body mass, while players in G6 had the lowest age and body mass values. The backs and line players were the tallest. In addition, the measurement of body mass showed that the line players had the highest body mass and BMI values. In conclusion, this study presented anthropometric data that differentiated levels of success in male handball teams playing in the 2013 world championships. This information should serve as a reference for the average standing stature, body mass, and BMI of handball players for particular positions at the professional level.